Alternative credit sources and green growth: The moderating role of internet usage popularity - Ngoc, Nguyen Bich; Thu, Nguyen Thi (Edelweiss Applied Science and Technology, 2025)
This paper investigates the impact of alternative credit sources on green growth in 74 countries from 2013 to 2019. The results of SGMM indicate that alternative credit sources (fintech and big tech) negatively impact green growth. However, the model results confirm the positive moderating significance of the proportion of customers using the internet on the relationship between alternative credit sources and green growth. For practical implications, countries should invest more in the development of technology infrastructure and the Internet’s level of access and popularity among the population. Moreover, to ensure the effectiveness of alternative credit sources, it is crucial to develop and implement regulations on the appraisal and supervision of green projects.